Degradation of Chloramphenicol Using UV-LED Based Advanced Oxidation Processes: Kinetics, Mechanisms, and Enhanced Formation of Disinfection By-Products - Xinlu Qu (MDPI AG, 2021)
As an emerging light source, ultraviolet light emitting diodes (UV-LEDs) are adopted to overcome the shortcomings of the conventional mercury lamp, such as mercury pollution. The degradation of chloramphenicol (CAP) using three UV-LED-based advanced oxidation processes (AOPs)—UV-LED/persulfate (UV-LED/PS), UV-LED/peroxymonosulfate (UV-LED/PMS) and UV-LED/chlorine—was investigated. Results indicate that CAP can be more effectively degraded by the hybrid processes when compared to UV irradiation and oxidants alone. Degradation of CAP using the three UV-LED-based AOPs followed pseudo-first-order kinetics. The degradation rate constants (kobs) for UV-LED/PS, UV-LED/PMS, and UV-LED/chlorine were 0.0522, 0.0437 and 0.0523 min−1, and the CAP removal rates 99%, 98.1% and 96.3%, respectively. The degradation rate constant (kobs) increased with increasing oxidant dosage for UV-LED/chlorine, whereas overdosing reduced CAP degradation using UV-LED/PS and UV-LED/PMS. Ultraviolet wavelength influenced degradation efficiency of the UV-LED based AOPs with maximum CAP degradation observed at a wavelength of 280 nm. The application of UV-LED enhanced the formation DBPs during subsequent chlorination. uUV-LED/PMS produced more disinfection by-products than UV-LED/PS. Compared to UV-LED, UV-LED/PS reduced the formation of dichloroacetonitrile and trichloronitromethane during chlorination owing to its capacity to degrade the nitro group in CAP. The intermediates dichloroacetamide, 4-nitrobenzoic acid, 4-nitrophenol were produced during the degradation of CAP using each of UV-LED, UV-LED/PS and UV-LED/chlorine. The present study provides further evidence supporting the application of UV-LED in AOPs.